Gambaran pengetahuan, sikap, dan tindakan masyarakat pesisir Kota Manado terhadap penggunaan obat - Shalomitha Aurel Karamoy; Angela Ftiriani Clementine Kalesaran; Eva Mariane Mantjoro (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Irrational drug use remains a public health concern and contributes to the increasing burden of antimicrobial resistance (AMR). Coastal communities have unique geographical and socio-cultural characteristics that may influence medication-use behavior. Purpose: To describe the knowledge, attitudes, and practices regarding medication use among coastal communities. Method: A descriptive observational design with a cross-sectional approach. The study was conducted in coastal areas of Manado City, including Sindulang I, Sindulang II, Bitung Karangria, Maasing, Tumumpa II, and Tongkeina. A total of 87 respondents were selected using purposive sampling. Data were collected through interviews using structured questionnaires and analyzed using univariate analysis. Results: Most respondents were female. Knowledge regarding medication use was predominantly categorized as poor (40.2%), followed by good (37.9%) and moderate (21.8%). The majority of respondents demonstrated positive attitudes toward medication use (75.9%). Drug-use practices were predominantly categorized as moderate (41.4%), followed by good (29.9%) and poor (28.7%). More than half of respondents (51.7%) reported purchasing or consuming medication without a doctor's prescription. Conclusion: Low drug literacy among Manado's coastal community, particularly regarding antibiotic usage, drug classification, and irrational drug use risks. Despite positive attitudes, practice remains moderate with high rates of unsupervised self-medication, highlighting a significant knowledge-to-practice gap that requires urgent health literacy interventions. Suggestion: Continuous health education on rational medicine use and stricter monitoring of prescription-only drug sales are urgently needed. Pharmacists and public health staff should enhance active counseling, while future research should employ analytical designs to identify the underlying factors driving community drug behavior. Keywords: Antibiotic; Antimicrobial; Coastal Community; Drug Use; Self-medication.